2017
DOI: 10.1111/1747-0080.12362
|View full text |Cite
|
Sign up to set email alerts
|

Post‐pyloric feeding tube placement in critically ill patients: Extending the scope of practice for Australian dietitians

Abstract: A dietitian can be trained to safely and successfully place PPFT in critically ill patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…Suitably skilled and experienced ICU dietitians, in the UK and internationally, can safely and successfully insert post-pyloric feeding tubes in these patients along with performing indirect calorimetry to enhance the nutrition assessment of the patient. 23,24 Leading international critical care dietitians are helping shape the evidence base for critical care nutrition by contributing to large multicentre nutritional trials such as the CALORIES trial 12 and international nutrition support guidelines. 11,25 Future for dietitians in critical care…”
Section: Current Impact Of the Critical Care Dietitianmentioning
confidence: 99%
“…Suitably skilled and experienced ICU dietitians, in the UK and internationally, can safely and successfully insert post-pyloric feeding tubes in these patients along with performing indirect calorimetry to enhance the nutrition assessment of the patient. 23,24 Leading international critical care dietitians are helping shape the evidence base for critical care nutrition by contributing to large multicentre nutritional trials such as the CALORIES trial 12 and international nutrition support guidelines. 11,25 Future for dietitians in critical care…”
Section: Current Impact Of the Critical Care Dietitianmentioning
confidence: 99%
“…Patients were admitted to the operative theater 2 (1-3) times during their ICU admission, with no difference in duration of operative-theater stay between the groups: .506 Received RRT, n (%) 6 ( 10) 2 ( 7) 4 (14) .424 Sepsis, n (%) 11 ( 19) 8 ( 27) 3 (10) .181 Pneumonia, n (%) 13 ( 22) 8 ( 27) 5 (17) .532 VAP specific, n (%) 13 ( 22) 8 ( 27) 5 (17) .…”
Section: Medical Therapymentioning
confidence: 99%
“…9 In critically ill patients with major burns, the preferred method of nutrient administration is via the enteral route. 8,10,11 Along with the decreased cost, compared with parenteral nutrition (PN), 11,12 the benefits of enteral nutrition (EN) include an improved immune response, the potential suppression of the hypermetabolic response, and the minimization of sepsis, 2,8,[11][12][13][14] all of which contribute to reduced mortality and hospital length of stay. 2,12 A systematic review and meta-analysis of 7 randomized controlled trials comprising 527 patients with major burns (>20% total body surface area [TBSA]) revealed that early feeding (≤24 hours after burn injury) was significantly associated with reduced mortality and clinical complications, such as rates of wound infection and protein catabolism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Australian dietetics profession has been active in this space over recent years and the number of advanced and extended practice roles and procedures introduced into the Australian health‐care setting continues to slowly grow. Published examples of the successful introduction of novel advanced and extended practice roles include a dietitian‐led gastroenterology clinic service, post‐pyloric feeding tube placement in critically ill patients, and dysphagia screening and intervention …”
Section: Introductionmentioning
confidence: 99%